Perfil del cuidador del paciente con enfermedad renal crónica: Una revisión de la literatura (2023)
Introduction: Caregivers of chronic kidney disease (CKD) patients have physical, social, economic, spiritual and emotional changes, derived from their role. Knowing the profile of the primary caregiver is essential to establish support and assistance interventions. Objective: To determine the profile of caregivers of CKD patients referred to in the literature, which describes the sociodemographic variables and the predominance of health conditions related to family care. Material and Method: A narrative review of the literature was carried out, following recommendations of the PRISMA statement. Primary studies (experimental or observational, quantitative and qualitative studies) about the health effects in the family caregiver of CKD patients were included. The databases ProQuest, ScienceDirect, Scopus, Dialnet, Redalyc and Scielo were consulted in the period between 2011 and 2018. Results: In relation to the sociodemographic characteristics of family caregivers, 41.66% are older than 53 years; 92.30% being female and 66.66% being married; with primary education in 26.08% and 22.22% of housewife occupation. In reference to the health effects, the emotional effects that prevail are anxiety and depression, followed by sleep disturbances, which affects the quality of life of the caregiver. Conclusion: The knowledge of the caregiver's sociodemographic variables allows to establish actions according to the needs and intervention of emotional effects, poor quality of sleep, social isolation, which affects the quality of life of the caregiver, and therefore, the patient. © 2019, Sociedad Espanola de Enfermeria Nefrologica. All rights reserved.